2015
DOI: 10.1017/dmp.2015.64
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Chronic Post-Traumatic Stress Disorder After Floods

Abstract: Objective: To explore the prevalence and determinants of chronic post-traumatic stress disorder (PTSD) among flood victims. Methods: A cross-sectional survey was carried out in 2014 among individuals who had experienced the 1998 floods and had been diagnosed with PTSD in 1999 in Hunan, China. Cluster sampling was used to select subjects from the areas that had been surveyed in 1999. PTSD was diagnosed according to DSM-IV criteria, social support was measured according to a Social Support Rating Scale, coping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 16 publications
(20 reference statements)
2
11
0
13
Order By: Relevance
“…Consistent with previous studies ( Bokszczanin, 2007 ; Chen et al, 2015 ; Dixon et al, 2015 ), our findings suggest that rainstorm-related experiences can directly lead to PTSD. This supports the shattered world assumption ( Janoff-Bulman, 2010 ), which proposes that traumatic experiences can challenge people’s stable belief systems such that more negative cognition and emotion emerges ( Janoff-Bulman, 1989 ), and in turn more PTSD symptoms are elicited.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies ( Bokszczanin, 2007 ; Chen et al, 2015 ; Dixon et al, 2015 ), our findings suggest that rainstorm-related experiences can directly lead to PTSD. This supports the shattered world assumption ( Janoff-Bulman, 2010 ), which proposes that traumatic experiences can challenge people’s stable belief systems such that more negative cognition and emotion emerges ( Janoff-Bulman, 1989 ), and in turn more PTSD symptoms are elicited.…”
Section: Discussionsupporting
confidence: 93%
“…Personality traits are traditionally conceptualized as dimensions of individual differences in tendencies to show consistent patterns of feelings, thoughts, and actions across developmental periods and contexts [ 59 ]. The interface between personality and psychopathology is well established, and the trait of neuroticism has been reported to be a predictor of many psychological disorders, including PTSD and anxiety [ 60 , 61 ]. In this study, participants with emotional instability, indicating a high level of neuroticism, were at a higher risk of suffering from PTSD and anxiety a long time after the flood.…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 ] This study showed the neuroticism (N) and psychoticism (P) are independent factors for PTSD symptom score, as in Holeva V's study. [ 39 ] There is strong correlation between PTSD and negative emotions, including neuroticism, avoidance, novelty-seeking, and self-transcendence, and hostility, anger, and anxiety. [ 40 ] These findings may assist in further uncovering the etiology, identification, and prevention strategies of PTSD.…”
Section: Discussionmentioning
confidence: 99%